Specific HLA alleles, paired with TCR V- and J-gene segment usage, link to distinct multiple myeloma survival rates. Issue 7 (7th June 2021) - Huda, Taha I.; Mihyu, Moody; Gozlan, Etienne C.; Arndt, Mary F.; Diaz, Michael J.; Zaman, Saif; Chobrutskiy, Boris I.; Blanck, George
Abstract: Multiple myeloma (MM) immunogenomics studies related to T-cell characterizations and involving large patient sets have been lacking, particularly in comparison to solid tumor types. Thus, we evaluated (i) HLA alleles, and (ii) T-Cell Receptor (TCR) V- and J-gene segment, HLA allele combinations, based on TCR recombinations in blood samples, for their potential associations with overall survival distinctions among an MM cohort. Two HLA alleles, and seven TCR V- or J-gene segment, HLA allele combinations were found to be associated with distinct overall survival rates. For examples, HLA-C*08:02, and the TRAV19, HLA-C*07:01 combination, were found to be associated with negative outcomes. In addition, anti-cytomegalovirus immune receptor sequences, from blood samples, were found to be associated with a positive outcome ( p = 0.012, n = 278). These data, and other related immunogenomics data, indicate a potential opportunity to use personal immunogenetics parameters as guides to prognosis and therapies.